Replication of live attenuated cold-adapted H2N2 influenza virus vaccine candidates in non human primates. Issue 1 (1st January 2015) - Broadbent, Andrew J.; Santos, Celia P.; Paskel, Myeisha; Matsuoka, Yumiko; Lu, Janine; Chen, Zhongying; Jin, Hong; Subbarao, Kanta
Highlights Non-human primates are more useful than mice or ferrets for evaluating LAIV virus replication. Cynomolgus and rhesus macaques are preferable for evaluating H2N2 LAIV candidate virus replication. Influenza A/Tecumseh/3/67 (H2N2) ca is a promising LAIV candidate for further evaluation.